Image repair strategies in trump’s self-defending speech in response to indictment: A pragmatic perspective - Ali Shakir, Nuha; Obayes Al-Azzawi, Qasim (Edelweiss Applied Science and Technology, 2024)
The present study examines the image repair strategies employed by former President Trump as a public response to the indictment against him in his (2023) Mar-a-Lago speech after his arrest and arraignment in New York court, which indicted him on 34 counts of falsifying business records. The current study aims at analyzing the types of image repair strategies and tactics employed as defense strategies to repair the damaged public image, identifying the types of speech acts used for realizing these strategies pragmatically according to the eclectic model developed for the analysis. The analysis reveals that three types of image repair strategies are used, namely: Denial, evasion of responsibility, and reduction of offensiveness, in which reduction of offensiveness is the most achieved strategy through the tactic of attacking the accuser as the frequently employed tactic, followed by the denial strategy in Trump’s speech. The realization of image repair tactics as pragmatic strategies is through triggering speech acts, the most frequently utilized SAs are the expressive SAs of criticizing and blaming, and the representative SAs of denying and accusing, that are used to realize the tactics of attack the accuser, simple denial and shift the blame pragmatically as SAs.